The art of teaching : best practices from a master educator - Allitt, Patrick N. (Great courses, 2010)
One of the most dynamic and innovative Great Courses we've ever produced, The Art of Teaching is designed to help you achieve new levels of success as a teacher. These 24 lectures will help you develop and enhance your teaching style; provide you with invaluable methods, tools, and advice for handling all manner of teaching scenarios; and open your eyes to how other teachersu2014and their studentsu2014think about and approach this life-changing profession.